Market madness : a century of oil panics, crises, and crashes - Clayton, Blake C. (Blake Carman), 1982- (New York, New York : Oxford University Press, 2015)
"In Market Madness, Dr. Blake Clayton, a Wall Street stock analyst and former Oxford researcher, draws on a century's worth of statistical data to offer a revolutionary new look the history of oil and future of energy. The culmination of a multi-year study, he shows how generational fears about an imminent, irreversible shortage of oil punctuate the history of oil since its earliest days. He explores the conditions in which oil supply fears arise, gain popularity, and eventually wane, and shows how important such stories can be in affecting financial markets. He links these episodes to the behavioral concept of irrational exuberance and new era economic thinking, first popularized by Nobel Laureate Yale economist Robert Shiller, to show how unfounded pessimism affects the market for oil and other exhaustible resources. Acknowledging the significant geological and structural changes the oil market has undergone over the last century, the book does not dismiss today's shortage fears out of hand, but asks what they reveal about how commodity markets function and what that means for investors and public officials. Clayton argues that the lessons to be learned from this history are the need for quality data about US and global oil reserves, the importance of clear communication from public officials about energy markets and resources, and the value of transparency in commodities markets. While these measures will not eliminate volatility and unpredictability in energy markets, he writes, they would mitigate unnecessary price spikes and improve investor and government decision-making. The book addresses popular debates in economics and finance on how mass beliefs affect financial markets while also offering a colorful narrative history for general readers about the dramatic booms and busts of the American oil industry"--
Machine generated contents note: -- CHAPTER 1 -- Introduction -- CHAPTER 2 -- "A National Crisis of the First Magnitude" -- The United States Geological Survey in an Era of Booming Demand, 1909-1927 -- CHAPTER 3 -- "A New Era of Scarcity and Higher Prices" -- Wartime Demand and the End of American Self-Reliance in Oil, 1940-1949 -- CHAPTER 4 -- "A Problem Unprecedented in Our History" -- American Anxiety in the Age of OPEC, 1970-1986 -- CHAPTER 5 -- "A Permanent Radical Rise in Oil Prices" -- Peak Oil Takes Wall Street, 1998-2013 -- CHAPTER 6 -- Conclusion.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Petroleum industry and trade -- United States -- History; Petroleum reserves -- United States -- History; Energy consumption -- United States -- History; Energy policy -- United States -- History; Electronic books